(untitled) (Journal of the College of Basic Education, 2025)
This study aims to identify (the effectiveness of the program in developing the skills of analyzing literary texts among students of the Arabic language departments in the faculties of education). To achieve this, the researcher chose a sample of (1275) male and female students in the fourth stage in the Arabic language departments in the colleges of education in Iraq. The researcher studied the experimental group by adopting the strategies of the proposed program and the control group using the traditional method. In order to identify the effectiveness of the proposed program in developing the skills of analyzing literary texts; The researcher adopted an experimental design with partial control, which is the design of the control group, with a pre and posttest. The researcher selected professors of literary text analysis among Iraqi university students, and third-stage students in Arabic language departments in colleges of education in Iraq, according to the proposed program, the first semester of the academic year 2022-2023. As for the research tool, the researcher prepared a test that measures the skills of analyzing literary texts. The test of analyzing literary texts included (40) items, of the type of multiple-choice questions. The researcher verified the validity and reliability of the test, and extracted the discriminatory powers. And coefficients of the difficulty of its paragraphs after presentation to a group of arbitrators. After that, the test was applied, before and after, to the students of the research sample. After analyzing the data, the research concluded that the experimental group was superior to the control group. In the light of the research results, the proposed program proved its effectiveness in developing the skills of analyzing literary texts among students of the Arabic language departments in the faculties of education. In the light of the results, the researcher recommended a set of recommendations, including the need to involve the current program as a teaching method in literature so that literature teachers (faculty members) can benefit from it, as it has proven very effective in the field of developing the skills of analyzing literary texts.